ICT literacy among teachers for integration in teaching and learning / Nor Famiza Tarsik - Tarsik, Nor Famiza; M Said, Salasiah; Hassim, Hasniza; Md Yatim, Norhidayu (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2019)
Information and Communication Technology (ICT) has been introduced to many aspects and widely used in many schools in Malaysia. The usage of ICT possibly will support not teaching and learning process at school but also assist teacher in manage daily task. Hence, this study aims to identify teachers’ behavioral of teachers to accept ICT in three secondary schools in Sungai Petani Kedah namely Sekolah Menengah Sungai Layar, Sekolah Menengah Khir Johari and Sekolah Menengah Ibrahim. The study propose to use quantitative methods to find out factors that influence the behavioral of teachers to accept ICT and teachers’ ICT integration levels in teaching and learning process. This study applies descriptive method and the basic reason for carrying out the descriptive research is to identify the acceptance of teachers towards ICT. This study is self-assessed by the respondents. Evidence is collected through modified questionnaire to collect quantitative data which is then analysed by the Statistical Product and Services Solutions programme. The result of the study may provide proper information and recommendation towards ICT development in school and among teachers.